A facile synthesis of bio-inspired hierarchical microstructure TiO2 :Characterization and photocatalytic activity - Turkten, Nazli; Karatas, Betul; Karatas, Yunus; Cinar, Zekiye; Bekbolet, Miray (WILEY, 2023)
Hierarchical photocatalysts have attracted notable concern due to their excellent features such as lower density, higher specific surface area, higher light-harvesting efficiency, and good surface permeability. Generally, such particular properties are achieved via the use of templates, preferentially focusing on natural biological materials. In this respect, rice husk (RH), an environmental waste containing elements C, N, S, and Si was used as a biotemplate to prepare TiO2 hierarchical microstructure photocatalyst (TiO2-HMP) along with TiO2 nanoparticle photocatalyst (TiO2-NP) by a facile sol-gel method. RH and the prepared TiO2 photocatalysts were characterized by using Fourier transform infrared (FTIR), X-ray powder diffraction (XRD), environmental scanning electron microscope-energy dispersive X-ray analysis (ESEM-EDAX), X-ray photoelectron spectroscopy (XPS), UV-visible diffuse reflectance spectroscopy (UV-DRS), photoluminescence (PL), and Brunauer-Emmett-Teller (BET) methods. The combination of RH and TiO2 via biotemplate strategy not only altered the band gap (E-bg = 2.74 eV) also slightly increased the surface area (similar to 10%). The photocatalytic activities of TiO2-NP and TiO2-HMP specimens were determined by degradation of 4-nitrophenol (4-NPh) under UV-A light irradiation. TiO2-HMP exhibited enhanced photocatalytic activity (>= 10%) compared to TiO2-NP most probably due to RH originated in-situ self-codoping by the presence of multidopant ions (C, N, S, and Si ions) as verified by EDAX elemental weight distribution profiles. These results demonstrated a beneficial use of an environmental waste in photocatalytic applications.
Keywords: biotemplate; photocatalysis; rice husk; sol-gel; TiO2 hierarchical microstructures; TITANIUM-DIOXIDE PHOTOCATALYSTS; RICE HUSK ASH; DOPED TIO2; MESOPOROUS SIO2-AT-TIO2; THERMAL-DEGRADATION; TIO2/SIO2 COMPOSITE; WATER-TREATMENT; METHYLENE-BLUE; HOLLOW SPHERES; SURFACE-AREA; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology